A Call to Action on Artificial Intelligence and Social Work Education: Lessons Learned from A Simulation Project Using Natural Language Processing. Issue 5 (19th October 2020) - Asakura, Kenta; Occhiuto, Katherine; Todd, Sarah; Leithead, Cedar; Clapperton, Robert
ABSTRACT: In discussing a university-industry partnership on the development of an Artificial Intelligence (AI)-based simulation platform, this conceptual paper explores the use of Natural Language Processing (NLP) as a pedagogical innovation in social work. Critically reflecting upon this ongoing project, we discuss the current promises and limitations of NLP for social work education. The Community of Inquiry (CoI) framework theoretically informs "lessons learned" from this case study and provides a call to action for social work educators to play a greater role in developing and researching pedagogies supported by currently evolving AI technologies.